Strategi Guru BK dalam Mengatasi Burnout Study Siswa SMKN 1 Widasari - Naelul Muna (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The purpose of this study was determine the factors of students experiencing burnout study, describing the teachers strategy in overcoming the burnout study of students SMKN 1 Widasari, and knowing the obstacles of BK teachers in overcoming the burnout study of SMKN 1 Widasari students. The method used in this research is descriptive qualitative, a data collection tool with observation, interview and documentation. Best on the results of the study that the factors that influence students experience burnout study is because 1) family factors, there are some students experiencing broken home, 2) factors teachers who do not like subjects, and 3) subjects that are not liked. The strategies of BK teachers in overcoming student burnout studies are 1) conducted an assessment, 2) individual counseling, 3) learning motivation and games that stimulate students to be enthusiastic in learning, and 4) group counseling (Kopdar). The constraints felt by BK teachers in their strategies to overcome students burnout studies are the lack of cooperation between subjects teachers, homeroom teachers and school principals.